SH+ 360: novel model for scaling up a mental health and psychosocial support programme in humanitarian settings. Issue 5 (1st September 2022) - Leku, Marx R.; Ndlovu, Jacqueline N.; Bourey, Christine; Aldridge, Luke R.; Upadhaya, Nawaraj; Tol, Wietse A.; Augustinavicius, Jura L.
Abstract : We explore multi-sectoral integration as a model for scaling up evidence-based mental health and psychosocial support interventions in humanitarian settings. We introduce Self Help Plus 360, designed to support humanitarian partners across different sectors to integrate a psychosocial intervention into their programming and more holistically address population needs.